2015
DOI: 10.1128/aac.03710-14
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Evaluation of the Activities of Six Parenteral Vancomycin Products Available in the United States

Abstract: A recent report found that generic parenteral vancomycin products may not have in vivo efficacies equivalent to those of the innovator in a neutropenic murine thigh infection model despite having similar in vitro microbiological activities and murine serum pharmacokinetics. We compared the in vitro and in vivo activities of six of the parenteral vancomycin products available in the United States. The in vitro assessments for the potencies of the vancomycin products included MIC/minimal bactericidal concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
7
2
Order By: Relevance
“…Pharmaceutical and therapeutic equivalence between the generic and original presentations of vancomycin was initially challenged [31,32], but recent data have shown that PK and PD differences in the six tested presentations were limited [74].…”
Section: Neonatologists Need Presentations and Formulations Adjusted Tomentioning
confidence: 99%
“…Pharmaceutical and therapeutic equivalence between the generic and original presentations of vancomycin was initially challenged [31,32], but recent data have shown that PK and PD differences in the six tested presentations were limited [74].…”
Section: Neonatologists Need Presentations and Formulations Adjusted Tomentioning
confidence: 99%
“…Thus, a heavily underpowered model in addition to the use of parametric statistic tests with non-Gaussian data, explain the failure of the experimental design to find significant differences [ 16 ]. The second paper is a study by Louie et al published in January 2015 [ 17 ], reporting the results from the evaluation of 6 vancomycin generics with FDA-demonstrated pharmaceutical equivalence: Hospira, Pfizer, APP, Sandoz, Baxter, and Mylan (Bioniche) in the mouse thigh infection model, trying to follow the methods employed by our group in the 2010 vancomycin paper [ 11 ]. The authors did not find differences across the products with regard to any in vitro evaluation or pharmacokinetic parameters, and the in vivo model yielded similar efficacy and potency.…”
Section: Introductionmentioning
confidence: 99%
“…Complex 1 was examined for its antimicrobial activity against S. aureus . The MIC was estimated by the broth dilution method in Luria Bertain broth using the standardized method 56 57 58 59 60 . Briefly, serial dilutions of complex 1 were prepared in distilled water with concentrations ranging from 1.8 to 57.6 ÎŒM.…”
Section: Methodsmentioning
confidence: 99%